Against the gods : the remarkable story of risk - Bernstein, Peter L. (John Wiley & Sons, 1998)
Against the Gods, a narrative that reads like a novel, chronicles the remarkable intellectual adventure that liberated humanity from the oracles and soothsayers by means of the powerful tools of risk management that are available to us today. This is a richly-woven tale of Greek philosophers and Arab mathematicians, of merchants and scientists, gamblers and philosophers, world-renowned intellects and obscure but inspired amateurs who helped discover the modern methods of putting the future at the service of the present, replacing helplessness before the fates with choice and decision.